2012
DOI: 10.3349/ymj.2012.53.6.1197
|View full text |Cite
|
Sign up to set email alerts
|

Total Intravenous Anesthesia with Propofol Reduces Postoperative Nausea and Vomiting in Patients Undergoing Robot-Assisted Laparoscopic Radical Prostatectomy: A Prospective Randomized Trial

Abstract: PurposeWe investigated the effect of total intravenous anesthesia (TIVA) with propofol on postoperative nausea and vomiting (PONV) after robot-assisted laparoscopic radical prostatectomy (RLRP) in patients at low risk of developing PONV, in comparison to balanced anesthesia with desflurane.Materials and MethodsSixty two patients were randomly assigned to the Des or TIVA group. Propofol and remifentanil were used for induction of anesthesia in both groups and for maintenance of the anesthesia in the TIVA group.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
1
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 29 publications
1
60
1
7
Order By: Relevance
“…A total of 13 trials reported pain intensity at or around 2 h postsurgery, in which 686 patients received anaesthesia using propofol for maintenance, while 668 were given inhalational anaesthesia [10,11,[18][19][20][21][22][23][24][25][26][27][28]. Overall, pain scores were not significantly different between experimental groups (Hedge's g (95%CI) À0.120 (À0.415-0.175) (p = 0.425) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 13 trials reported pain intensity at or around 2 h postsurgery, in which 686 patients received anaesthesia using propofol for maintenance, while 668 were given inhalational anaesthesia [10,11,[18][19][20][21][22][23][24][25][26][27][28]. Overall, pain scores were not significantly different between experimental groups (Hedge's g (95%CI) À0.120 (À0.415-0.175) (p = 0.425) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A total of nine trials reported pain intensity at or around 24 h postsurgery, in which 595 patients received propofol anaesthesia, while 586 had inhalational anaesthesia [10,11,18,19,21,22,25,28,29]. Overall, compared with inhalational anaesthetics, patients who received propofol reported significantly lower pain scores 24 h postsurgery (Hedge's g (95% CI) À0.134 (À0.248 to À0.021) (p = 0.021) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Segundo um estudo realizado em macacos da espécie Macaca mulatta, demonstrou que o tempo de recuperação anestésica após contenção química utilizando propofol (6mg/kg/IV) foi de 22,5 ± 3,2 minutos, ligeiramente inferior quando comparado à associação cetamina (8mg/kg/IM) midazolam (0,2 mg/kg/IM), que durou 41,2 ± 5,9 minutos. O propofol tem sido amplamente utilizado em protocolos de anestesia intravenosa, sendo seu uso muito difundido na Medicina Veterinária e humana (SUAREZ et al, 2012, YOO et al, 2012.…”
Section: Introductionunclassified
“…In this trial, the highest NRS pain score for the wound site was slightly, but non-signi cantly, lower in the IV propofol group, both during coughing and at rest. Thirdly, propofol signi cantly reduces PONV compared with inhalational anesthetics (25). The anti-emetic effect of propofol is associated with inhibition of the 5-hydroxy-tryptamine-3 (5-HT) receptors in the serotonergic system, dopaminergic (D2) receptors in the chemoreceptor trigger zone, and the limbic system (22,26).…”
Section: Discussionmentioning
confidence: 99%